COMPARISON OF QUALITY-OF-LIFE DOMAINS USING WHOQOL-BREF IN LEPROSY PATIENTS: A SYSTEMATIC REVIEW - Mohd Salleh, Farida Nazahiya; Shahrom, Muhammad Ezmeer Emiral; Jaimon, Selly; Syed Abdul Rahim, Syed Sharizman; Saupin, Saihpudin @ Sahipudin; Atil, Azman; Abd Rahim, Muhammad Aklil (Malaysian Journal of Public Health Medicine, 2025)
Leprosy is a disease caused by Mycobacterium leprae, affecting the skin, peripheral nerves, eyes, mucous membranes, and other systems. Due to physical disfigurement, disabilities, pain, discomfort, stigma, prejudice, and discrimination, the patients are vulnerable to experiencing a low Quality of Life (QoL). This systematic review aimed to compare the QoL among leprosy patients across geographical and sociodemographic contexts using the World Health Organisation Quality of Life Brief Version (WHOQOL-BREF) questionnaire. It also aims to determine which domains in the WHOQOL-BREF were the most severely affected by leprosy. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 Checklist, and all criteria related to a systematic review were reported. A structured literature search used three databases: PubMed, Science Direct, and Scopus. The risk bias assessment method used the Mixed Methods Appraisal Tool (MMAT). All studies met the quality criteria between 80 and 100%. Six papers were included from 844 articles identified. All studies were conducted in upper-middle-income countries such as Brazil, Indonesia, and China. The four domains assessed in the WHOQOL-BREF were physical, psychological, social relationships, and environmental. The most severely affected domain in the WHOQOL-BREF was the environmental domain. Three out of the six studies had the lowest score in the environmental domain, with scores ranging from 50.00 to 56.00. The components affected in the environmental domain were related to the home environment, basic amenities, living conditions, financial stability, information availability, and accessibility to social and healthcare services. Notably, targeted interventional programmes should be developed, focusing on the most affected domain in the WHOQOL-BREF to improve the QoL of leprosy patients.